Unraveling Morphophysiological and Biochemical Responses of Triticum aestivum L. to Extreme pH: Coordinated Actions of Antioxidant Defense and Glyoxalase Systems - Bhuyan, M. H. M. Borhannuddin; Hasanuzzaman, Mirza; Mahmud, Jubayer Al; Hossain, Md. Shahadat; Bhuiyan, Tasnim Farha; Fujita, Masayuki (Plants (Basel), 2019)
Soil pH, either low (acidity) or high (alkalinity), is one of the major constraints that affect many biochemical and biological processes within the cell. The present study was carried out to understand the oxidative damage and antioxidant defense in wheat (Triticum aestivum L. cv. BARI Gom-25) grown under different pH regimes. Eight-day-old seedlings were exposed to growing media with different pH levels (4.0, 5.5, 7.0, and 8.5). Seedlings grown in pH 4.0 and in pH 8.5 showed reductions in biomass, water, and chlorophyll contents; whereas plants grown at pH 7.0 (neutral) exhibited a better performance. Extremely acidic (pH 4.0) and/or strongly alkaline (pH 8.5)-stress also increased oxidative damage in wheat by excess reactive oxygen species (ROS) generation and methylglyoxal (MG) production, which increased lipid peroxidation and disrupted the redox state. In contrary, the lowest oxidative damage was observed at a neutral condition, followed by a strong acidic condition (pH 5.5), which was mainly attributed to the better performance of the antioxidant defense and glyoxalase systems. Interestingly, seedlings grown at pH 5.5 showed a significant increase in morphophysiological attributes compared with extreme acidic (pH 4.0)- and strong alkaline (pH 8.5)-stress treatments, which indicates the tolerance of wheat to the acidic condition.